The Effectiveness of Learning Models Problem Solving on Electrolyte and Nonelectrolyte Solutions to Improve Science Process Skills - Ila Rosilawati; Rima Damayanti; Nina Kadaritna (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
The purpose of this research was to describe the effectiveness of a problem solving learning model on electrolyte and non electrolyte solution material. The method used was a quasi-experiment with the matching only pretest-posttest control group design. The population on this research was all of the students from Senior High School Al-Azhar 3 Bandar Lampung in grade X IPA. The research sample was determined by purposive sampling technique, in order to obtain class X IPA 4 as the experimental class and X IPA 3 as the control class. The data analysis technique used is the difference test of two means using the t-test. The results showed that the n-gain mean of science process skills in the experimental class (0.67) was in the medium category; There is a significant difference in the average posttest score of science process skills between the experimental class and the control class. Thus, it can be concluded that the problem solving learning model on electrolyte and non-electrolyte solution material is effective for increasing students' science process skills. Keywords: electrolyte and non-electrolyte solutions, science process skills, problem solving learning models.